1989
DOI: 10.1007/bf00544528
|View full text |Cite
|
Sign up to set email alerts
|

The high temperature creep deformation of Si3N4-6Y2O3-2Al2O3

Abstract: The creep properties of silicon nitride containing 6 wt% yttria and 2 wt% alumina have been determined in the temperature range 1573 to 1673 K. The stress exponent, n, in the equation e « a , was determined to be 2.00 +_0.15 and the true activation energy was found to be 692 +_ 25 kJ mol~. Transmission electron microscopy studies showed that deformation occurred in the grain boundary glassy phase accompanied by microcrack formation and cavitation. The steady state creep results are consistent with a diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 39 publications
(42 reference statements)
2
22
2
Order By: Relevance
“…It is obvious that the accommodation process here is the solution-precipitation process because of the slight grain growth and elongation of β-Si 3 N 4 grains. Furthermore, the present experimental activation energy of 571.8 kJ/mol, which corresponds to that for the diffusion of nitrogen ions through the grain boundary glassy phase [36], is similar to other values reported for the deformation of Y 2 O 3 /Al 2 O 3 -doped silicon nitride materials for the grain boundary sliding mechanism accommodated by a diffusion-controlled solution-precipitation process [36,37]. The solution-precipitation process in fine-grained ceramics can be controlled by either an interface reaction or by diffusion in the liquid.…”
Section: Deformation At High Stressessupporting
confidence: 60%
“…It is obvious that the accommodation process here is the solution-precipitation process because of the slight grain growth and elongation of β-Si 3 N 4 grains. Furthermore, the present experimental activation energy of 571.8 kJ/mol, which corresponds to that for the diffusion of nitrogen ions through the grain boundary glassy phase [36], is similar to other values reported for the deformation of Y 2 O 3 /Al 2 O 3 -doped silicon nitride materials for the grain boundary sliding mechanism accommodated by a diffusion-controlled solution-precipitation process [36,37]. The solution-precipitation process in fine-grained ceramics can be controlled by either an interface reaction or by diffusion in the liquid.…”
Section: Deformation At High Stressessupporting
confidence: 60%
“…Todd and Xu. 32 reported approximately 700 kJ/mol for the activation energy for the diffusion of nitrogen ion through the grain boundary.…”
Section: Creep Mechanism-activation Energymentioning
confidence: 98%
“…It cannot tolerate the large deformation necessary to undergo tertiary creep without failure. However, a few studies of creep of Si 3 N 4 in four‐point bending have shown tertiary creep regions 68 . Secondary, or steady‐state creep is the most studied, because the other two regions are transient and depend on numerous factors.…”
mentioning
confidence: 99%
“…Tensile Creep: Creep deformation in tension is attributed to viscous flow of the intergranular phase and dilation of the structure so that rigid grains may slide past each other 65,74 . Unaccommodated strain in tension is the result of cavity formation, both at multigrain junctions and along the boundaries between grain pairs 24,65,66,68,71,75,76 . Cavities are nucleated to relieve the stresses that build up as a result of viscous flow and grain boundary sliding, 76 and are most commonly found at multigrain junctions.…”
mentioning
confidence: 99%